Pengaruh Gaya Kepemimpinan, Budaya Organisasi dan Lingkungan Kerja Terhadap Disiplin Kerja Pegawai Dinas PPKBP3A Kabupaten Sukoharjo - Wahyu Nugroho; Sutarno Sutarno (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study examines the influence of leadership style, organizational culture, and work environment on employee work discipline at the Population Control, Family Planning, Women's Empowerment, and Child Protection Agency of Sukoharjo Regency. The research employs a quantitative approach, utilizing primary data collected through questionnaires. The study's population consists of 37 employees, and due to the limited number of respondents (less than 100), a saturated sampling technique was applied, ensuring the inclusion of all members in the study.The research utilizes multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²) as statistical analysis techniques. The t-test results reveal that leadership style (X1) does not have a significant effect on employee work discipline, whereas organizational culture (X2) and work environment (X3) have a significant positive influence. The F-test results confirm that the regression model used in this study is appropriate for explaining the relationship between independent and dependent variables. Additionally, the R² test results indicate the proportion of variance in employee work discipline that can be explained by the independent variables.The findings suggest that fostering a strong organizational culture and improving the work environment can enhance employee work discipline. Meanwhile, leadership style alone does not significantly impact discipline levels. The study recommends that organizations prioritize developing a supportive work culture and conducive work environment while reassessing leadership strategies to align with employee needs. These insights provide valuable implications for policymakers and organizational leaders aiming to improve workforce discipline and productivity.